Cricket/Mica2 Based Discrete Event Simulator for WiHoc Ver.l.O Localization Analysis - Subramaniam, Shamala; T., Sangeetha; A., Moqry (2009)
The deployment of Wireless Sensor Networks (WSN) has enabled applications to operate at its optimum and maximum potential. This paper presents the enhancement of the Wireless Hockey (WiHoc) System ver.l.O. The sensors are utilized to acquire the movement of field hockey players on a coaching strategy board. These are denoted and executed by the Cricket I Mica-2 sensors which have been utilized as the COfe hardware of the developed system. A software to enable coordinate derivation for the field hockey localization is further developed to relate the localization information to the hockey Grid. In addition, the details of a proposed and developed Discrete Event Simulator (DES) to analyze the performance analysis ofWiHoc is deliberated extensively. The developed simulator is analyzed utilizing the accuracy metric. The correlation of the DES has enabled optimized operations of the WiHoc system, which have been demonstrated by the extensive experiments conducted.